Before I fall [videorecording (DVD)] - Deutch, Zoey, 1994-; Sage, Halston, 1993-; Miller, Logan, 1992-; Oliver, Lauren, 1982- (Universal Pictures Home Entertainment, 2017)
After one fateful night, Sam wakes up with no future at all. Trapped reliving the same day over and over, she begins to question just how perfect her life really was. And as she begins to untangle the mystery of a life suddenly derailed, she must also unwind the secrets of the people closest to her, and discover the power of a single day to make a difference, before she runs out of time for good.